Persistent Paradoxical Reaction to Midazolam despite General Anesthesia with Dexmedetomidine - Sarah Park; Mariam Ibrahim; Augusto Torres (Case Reports in Anesthesiology)
Midazolam is a widely used benzodiazepine due to its rapid onset of action and relatively safe side effect profile. It is used for sedation, anxiolysis, and induction of general anesthesia. However, in <1% of instances, it may cause a paradoxical excitement: agitation, restlessness, myoclonus, stiffening of the limbs, and aggression. We report a case report in which preoperative administration of midazolam caused onset of the aforementioned symptoms that were not attenuated by general anesthesia with dexmedetomidine. This case report aims to create awareness about the rare adverse reactions of midazolam and prepare clinicians to manage these situations.